Essential and Vulnerable: Implications of Covid-19 for Farmers in Ireland. Issue 4 (1st October 2020) - Meredith, David; McNamara, John; van Doorn, Diana; Richardson, Noel
ABSTRACT: Objectives : This paper seeks to: provide an overview of the impacts of and responses to the spread of COVID-19 in Ireland; assess the vulnerability of the population living in rural areas to COVID-19; compare the health status of male farmers to underlying medical conditions frequently associated with those experiencing the worst impacts of the illness; and assess the implications of COVID-19 for farmers living alone and farm households with children. Methods : We present an overview of the impact and response to COVID-19 through the use of public health statistics and reference to policy documents. We subsequently draw on the results of ongoing geographic and health research to present an overview of the impacts and potential implications of COVID-19. Results : The population of many rural areas and farmers in particular are highly vulnerable to adverse outcomes to COVID-19 infection. Single person farm households are at particular risk of isolation, whilst those families with children are at increased risk of stress. Conclusions : There is an urgent need to address both COVID-19 challenges and the health and wellbeing issues confronting farmers and farm families arising out of the current pandemic by supporting these populations adopt and sustain health behaviour changes, improve their wellbeing and develop the resources that support resilience.